VIOLATION OF THE PROSECUTOR'S PROFESSIONAL CODE OF ETHICS IN THE VIEW OF ISLAMIC LAW AND ITS APPLICATION IN COURT - Gaffar, Azis; Ramadhan, Narendra Jumadil Haikal (Al-Masail: Journal of Islamic Studies, 2024)
The profession of a prosecutor carries significant responsibilities in upholding the law, maintaining justice, and protecting public interests. The professional code of ethics for prosecutors serves as a crucial guideline to ensure these duties are carried out with integrity, honesty, and professionalism. However, challenges often arise in the form of moral and ethical dilemmas during the execution of their duties. This journal examines the professional code of ethics for prosecutors from the perspective of Islamic law and its application in courts. The research method employed is a normative approach with a comparative analysis between the principles of Islamic law and the guidelines of the professional code of ethics for prosecutors in Indonesia. In Islamic law, the concepts of justice (al-‘adl), trustworthiness (amanah), and integrity are fundamental principles that must be upheld by prosecutors as legal enforcers. These values align with the principles of professionalism in the prosecutor's code of ethics, such as independence, responsibility, and honesty. This study concludes that integrating Islamic ethical values into the application of the professional code of ethics for prosecutors can enhance the quality of law enforcement, making it more just, dignified, and morally grounded. Recommendations include implementing Sharia-based ethical training for prosecutors, stricter periodic oversight, and the establishment of an ethics committee grounded in Islamic values to support the implementation of the code of ethics. Through this approach, it is hoped that prosecutors' professionalism will be maintained, and public trust in the judicial system will increase.